2013
DOI: 10.12657/denbio.071.014
|View full text |Cite
|
Sign up to set email alerts
|

Towards the propagation of a critically endangered tree species Anisoptera scaphula

Abstract: Anisoptera scaphula (Roxb.) Kurz, the tallest tree species in Bangladesh, is critically endangered worldwide due to its poor natural regeneration. This study describes the appropriate regeneration technique for A. scaphula through seed germination and clonal propagation by stem cutting. The fastest and highest germination percentage (65) was observed in dewinged seeds sown inverted orientation with half buried position (T10) followed by dewinged seeds (62.5%) sown horizontally in full buried (T7) and delayed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…However, the mean leaf number of rooted cuttings was insensitive to IBA treatment (Table 1). This was in accordance with the reports from Hossain et al (2014bHossain et al ( , 2019 as they found significantly higher survival of rooted cuttings for A. scaphula and P. neriifolius in nursery with IBA treatment over control. Also, Hossain et al (2011) obtained the highest (85%) survival in the F. jangomas cuttings treated with 0.4% IBA and the lowest in control.…”
Section: Survival Of E Rheedii Rooted Cuttingssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the mean leaf number of rooted cuttings was insensitive to IBA treatment (Table 1). This was in accordance with the reports from Hossain et al (2014bHossain et al ( , 2019 as they found significantly higher survival of rooted cuttings for A. scaphula and P. neriifolius in nursery with IBA treatment over control. Also, Hossain et al (2011) obtained the highest (85%) survival in the F. jangomas cuttings treated with 0.4% IBA and the lowest in control.…”
Section: Survival Of E Rheedii Rooted Cuttingssupporting
confidence: 93%
“…Applied rooting hormone IBA is known to intensify the rooting ability of cuttings explained by several authors. For instance, Hossain et al (2014b) reported the highest rooting percentages (63%) and maximum number of root (4.8) per cutting when single node cuttings of Anisoptera scaphula stem were treated with 0.8% IBA solution followed by 0.4% IBA and the lowest was in control. Similar result was reported by Hossain et al (2019) for Podocarpus neriifolius D. Don.…”
Section: Rooting Ability Of E Rheedii Stem Cuttingmentioning
confidence: 99%